Patient Health Questionnaire (PHQ-9): psychometric evidence in Piuran university students - Arellano Vilela, Geraldine Luciana (2021)
The present research work sustained the purpose of studying the psychometric properties of the Patient Health Questionnaire (PHQ-9) in university students from Piura. For its execution, a sample of 300 university students whose ages fluctuate between 16 and 30 years was used. The results present evidence of validity of the internal structure, (X2 / gl = 3.683, CFI = 0.923 and RMSEA = 0.095). Similarly, the reliability values of ordinal Alpha with 0.899 and McDonald's Omega with 0.87 were found, indicating adequate values.